Development of a Management Guide Module for Vocational Secondary School Concrete Workshop Practical Tools and Materials - Suwandi, Fakhri Fauzi; Supraptono, Eko; Anis, Samsudin (Journal of Vocational and Career Education, 2023)
The quality of management in the practical workshop area determines the quality of practical activities in it. Teachers need to prepare a good workshop implementation process by paying attention to everything, starting from the effectiveness of implementation to achieving implementation that provides good habits for students in it. In this case, the thing that is being considered is the implementation of the 5S/5R culture.This research uses Research and Development using the ADDIE development model. The assessment of the suitability of the media being developed is carried out by a judgment expert. The product trial was carried out at SMK Negeri 2 Salatiga with 36 students in the experimental class. Data collection from experts uses material and media validation instruments for product suitability, while data collection on application to students uses teacher assessment through observation instruments and checklist data by researchers to test product effectiveness.The results of this research show (1) that the product developed is a module for management of tools and materials for Vocational High School concrete workshops; (2) The product is declared valid and reliable using the Aiken v test and expert percentage. (3) the module was developed practically based on responses from Experts/Validators consisting of lecturers and teachers practicing Construction and Housing Engineering (4) effectiveness testing using the N Gain test showed that the data for the experimental and control classes had increased with a percentage of 47.59%.